An autoethnography on Diaohua Chang / Wang Lei - Wang, Lei (2019)
This dissertation focuses on an autoethnographical account of Diaohua Chang in Kuala Lumpur with a case study at three nightclubs. Diaohua Chang is a live-singing performance of Chinese popular songs common to venues such as open-air food court and night clubs. The present research studied Diaohua Chang at nightclub setting. The selected nightclubs host Diaohua Chang, a live singing performance on a stage in a Karaoke Pub setting. There is a serious lack of studies on Diaohua Chang. Related past literature such as Tan (1984), Chang (2014) and Chin (2015) described the cultural elements of the sing-song performances of Getai and Hua Chang, however most are from an outsider perspective. In this study, the author explored the very much female dominated Diaohua Chang from an insider and male perspective in an auto-ethnographical tradition. This dissertation aims to provide a holistic view and discussion on Diaohua Chang and its social and gender issues with a self-reflexive account of the author’s participant observation at the field.